CORELATION OF CRITICAL THINKING ABILITY TO LEARNING ACTIVITY AFTER FLIPPED CLASSROOM-PjBL LEARNING MODEL APPLICATION - Firdiawan Ekaputra (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2023)
This study aimed to determine the correlation of critical thinking skills with learning activities after the application of the flipped classroom-PjBL learning model. The sample used in this study were students who took the assessment of the process and learning outcomes of chemistry class C in the 2022/2023 academic year of the Jambi University Chemical Education Study Program. The research method used is the correlation method with a quantitative approach. Research data were obtained using a questionnaire before and after the application of the flipped classroom-PjBL learning model to data on critical thinking skills and student learning activities. The questionnaire on critical thinking consists of 5 statements, while the questionnaire on learning activity consists of 10 statements. Data regarding critical thinking skills and learning activities were carried out Pearson correlation test to determine the relationship between the dependent variables, the correlation level of critical thinking skills and learning activities was carried out product-moment correlation test. The results of this study are that there is a very good correlation between students' critical thinking skills and learning activities after the application of the flipped classroom-PjBL learning model, the correlation level of critical thinking skills to learning activities is very high with a value of 0.813.